Proteomic and phospholipidomic characterization of extracellular vesicles inducing tumor microenvironment in Epstein‐Barr virus‐associated lymphomas. Issue 4 (15th March 2021) - Ito, Masatoshi; Kudo, Kai; Higuchi, Hiroshi; Otsuka, Hiroko; Tanaka, Masayuki; Fukunishi, Nahoko; Araki, Takuma; Takamatsu, Masako; Ino, Yoko; Kimura, Yayoi; Kotani, Ai
Abstract: Epstein‐Barr virus (EBV) causes malignant carcinomas including B cell lymphomas accompanied by the systemic inflammation. Previously, we observed that phosphatidylserine (PS)‐exposing subset of extracellular vesicles (EVs) secreted from an EBV strain Akata‐transformed lymphoma (Akata EVs) convert surrounding phagocytes into tumor‐associated macrophages (TAMs) via induction of inflammatory response, which is in part mediated by EBV‐derived micro RNAs. However, it is still unclear about EV‐carried other potential inflammatory factors associated with TAM formation in EBV lymphomas. To this end, we sought to explore proteomic and phospholipidomic profiles of PS‐exposing EVs derived from EBV‐transformed lymphomas. Mass spectrometric analysis revealed that several immunomodulatory proteins including integrin αLβ2 and fibroblast growth factor 2 (FGF2) were highly expressed in PS‐exposing Akata EVs compared with another EBV strain B95‐8‐transformed lymphoma‐derived counterparts which significantly lack TAM‐inducing ability. Pharmacological inhibition of either integrin αLβ2 or FGF2 hampered cytokine induction in monocytic cultured cells elicited by PS‐exposing Akata EVs, suggesting the involvement of these proteins in EV‐mediated TAM induction in EBV lymphomas. In addition, phospholipids containing precursors of immunomodulatory lipid mediators were also enriched in PS‐exposing Akata EVs compared with B95‐8 counterparts. Phospholipidomic analysis of fractionated Akata EVs by density gradient centrifugation further demonstrated that PS‐exposing Akata EVs might be identical to certain Akata EVs in low density fractions containing exosomes. Therefore, we concluded that a variety of immunomodulatory cargo molecules in a certain EV subtype are presumably conducive to the development of EBV lymphomas.